A Tale of Two Banks: When Credit Loss Models Meet Economic Crises - CHEN, CHEN; HUANG, DIFANG (Journal of Accounting Research, 2026)
ABSTRACT Policy makers and researchers are concerned that the expected credit loss (ECL) approach may exacerbate procyclicality. Using administrative loan‐level and firm‐level data in China, we find that banks adopting the ECL model reduced their credit supply and became more prudent in lending decisions after the onset of the COVID‐19 pandemic, compared to banks using the incurred credit loss (ICL) approach. Our findings are more pronounced for banks that experienced greater loan loss provisions induced by ECL and for firms with higher credit risk. The credit contraction persisted throughout our sample period. We further document that firms more exposed to ECL banks experienced larger reductions in loans, assets, liabilities, and revenue after the pandemic began than those more exposed to ICL banks. These findings support the conjecture that the ECL approach may exacerbate procyclicality.